Judicial Preview on the Bill on International Treaty Ratification - Sidharta, Noor; Sudarsono, Sudarsono; Nurjaya, I Nyoman; Sugiri, Bambang (The Constitutional Court of the Republic of Indonesia, 2017)
This research is aimed to find and introduce a new idea on the state administration, which has implications on the international treaty ratification procedure followed by Indonesia and additional authorizations of the Constitutional Court of the Republic of Indonesia. The judicial preview in this research is an international treaty examination procedure by the Constitutional Court before an international treaty is transformed into a law, i.e. such international treaty is a Bill. The judicial preview shall have different terms in each country, such as Review ex ante, abstract review, judicial review. This procedure is applied when an international treaty has not been validated as a countryâs national law. The benefits of a judicial preview shall be a solution to connect an ambiguity between the state administrative law and international law. The judicial preview is also the inter-state institutions real check and balance on the international treaty. Out of benchmarking results of four countries following the monism doctrine, i.e. Russia, Germany, France, and Italty and two countries following the dualism doctrine, i.e. Hungary and Ecuador, several additional authorizations of the Constitutional Court shall be summarized, i.e. via the Amendment of 1945 Constitution of the Republic of Indonesia and/or regulations via laws. If both manners are not possible, the Constitutional Court may apply the judicial preview as a state administrative practice. An international treaty draft, which has passed through the judicial preview, may not be submitted to the Constitutional Court to be performed a judicial review, unless 5 (five) year-period has passed since the bill is enacted as a law.